Volatile Compounds in Effective Bait: Microbiological and Chemometric Approaches - Mohamed, Prof. Ts. Dr. Saiful Bahri; Ghazali, Prof. Madya Dr. Puspa Liza; Baig, Prof. Madya Dr. Atif Amin (CreateSpace Independent Publishing Platform, 2017)
House flies are commonly found at homes and business premises in Malaysia. They are known as vectors of pathogen because they carry the pathogenic bacteria such as Escherichia coli and salmonella. In doing so, various kinds of baits are used to attract and trap these flies either by mechanical or chemical means. But all these baits are not capable of attracting flies equally and its hygienic status is very important to human and pets when contacting directly with them. The main goal of this study is to find out the best bait that can attract house fly effectively and safely in every place, and its hygienic condition including effective time duration of the best bait performance. Experiments were conducted to determine and justify the best bait among six different baits commonly used in Malaysia. Two baits made in abroad and four baits made in Malaysia that are commonly used were selected for conducting this study. A simple, low-cost bottle trap technique was chosen to carry out the experiments in food industry, fish market and poultry farm in the east coast of Malaysia. The experimental data were used to determine the best bait. The hygienic condition of the best bait was determined by using a spread plate method under selective media such MRS agar, Eosin Methylene Blue (EMB) agar, and Dichloran Rose Bengal Chlortetract Cycline (DRBC) agar. Furthermore, Chemometric analysis (cluster analysis CA & discriminant analysis DA) and spread plate bacteria analysis on Nutrient Agar (NA) were done in order to determine the effective time for the best performance of the best bait. The spread plate bacteria analysis on NA was done for day 2, 3 and 4 only. Each time effective analysis was done by using eight discriminant variables: 30 minutes, 2 hours, 4 hours, 6 hours, 8 hours, 12 hours, control CEFCT powder, and control molasses (p < 0.05). It was found that Chinese Electronic Fly Catcher Trap (CEFCT) bait is the most effective one which can trap more house flies compared to other baits. It was also found through hygienic study that no significant growth of E.coli, Lactobacilus yeasts and moulds were formed in four days incubation period at 37o C. Hence, the CEFCT bait can be used safely. It was also observed that the CEFCT bait can be enabled its time effectiveness through CA and DA into three groups of time effectiveness given by correct classification (100%, 75%, and 75%). Bioassays analysis shows that CEFCT bait were very active up to 30 minutes through CFU count (9.28, 9.34, and 9.35 lofcfu/ml). The CEFCT bait is very much useful in trapping house flies and not harmful to human and animal health. Further studies are necessary to find low-cost bait components with similar effect of the best bait (CEFCT) in local markets in order to develop a new low cost bait.